Diffusion-Weighted Imaging of the Brain: Beyond Stroke. Issue 2 (May 2017) - Dmytriw, Adam A.; Sawlani, Vijay; Shankar, Jai
Diffusion-weighted imaging provides image contrast that is different from that provided by conventional magnetic resonance imaging techniques. It is highly sensitive for detection of cytotoxic oedema, and as such has gained favor in the detection of acute infarcts. However, diffusion-weighted imaging is underrepresented in the characterisation of many other disease processes. Our objective is to differentiate diseases that manifest with various neurological disorders, based on diffusion contrast and apparent diffusion coefficient values and review of hyper- and hypointense lesions on diffusion-weighted imaging.